ANALYSIS OF FACTORS AFFECTING THE BRAND LOYALTY: STUDY IN CONSUMER BRAND SOAP Rinso IN YOGYAKARTA - Muriani, Ari; Lastari, SE, Siwi; Darini, M. Si, MM. Dra. Sri (Management, 2010)
Abstraction is a brief description of research. This study investigates the influence of brand predictability (predictability brand), brand liking (favorite brand), brand competence (competence brand), brand reputation (brand reputation), and trust in the company (trust company) of soap brand loyalty Rinso. This study will look at brand loyalty Rinso in two shopping centers in the DI Yogyakarta is Gardena and Alfa Gudang Rabat. The population of this research is all Rinso detergent soap users who live in Yogyakarta Special Region. The samples in this study carried out by non-probability sampling is convenience sampling (most easily found) and purposive sampling (who buy Rinso) in shopping malls and supermarkets: Gardena and Alfa Gudang Rabat. Methods of data analysis used is regression analysis. The results found that the five variables, namely brand predictability (predictability brand), brand liking (favorite brand), brand competence (competence brand), brand reputation (brand reputation), and trust in the company (trust in the company) has significant positive influence to brand loyalty. Key words: brand loyalty, predictability brand, brand preferences, brand competence, reputation, brand, confidence in the company. keyword: brand,loyalty,competence